2017
DOI: 10.17531/ein.2017.2.9
|View full text |Cite
|
Sign up to set email alerts
|

The probabilistic analysis and optimal design of a bevel gear transmission system with failure interaction

Abstract: Article citation info: IntroductionGenerally, multiple failure modes may occur in a gear transmission system. Due to the common-source of the input random variables of the system, such as the external loads, the geometric parameters and the material properties, the existing failure modes would be correlated to a certain extend [2,13]. From another perspective, it means that a failure may cause another failure occurs more rapidly, or just the opposite. Actually, whether the dependence of different failure modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Wang et al (2016) demonstrated the multi-objective optimization of cycloid gears using GA. Volume and efficiency were the objective functions considered. Hao and Zhencai (2017) presented a model to investigate the impact of copulas for designing structure between various failure modes of bevel gear under incomplete probability. It has been found that the probability of failure for different copulas differs from each other.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2016) demonstrated the multi-objective optimization of cycloid gears using GA. Volume and efficiency were the objective functions considered. Hao and Zhencai (2017) presented a model to investigate the impact of copulas for designing structure between various failure modes of bevel gear under incomplete probability. It has been found that the probability of failure for different copulas differs from each other.…”
Section: Introductionmentioning
confidence: 99%